Corrosion- and wear-resistant composite film of graphene and mussel adhesive proteins on carbon steel. (March 2020) - Cheng, Jie; Chen, Sulin; Zhang, Fan; Shen, Bin; Lu, Xinchun; Pan, Jinshan
Highlights: Green and multifunctional composite film using mussel adhesive protein and graphene. Mefp-1/graphene film provides enhanced corrosion protection for carbon steel. Corrosion protection is due to interaction between graphene, Mefp-1 and Fe(III). Graphene film shows good adhesion, lubricity and wear resistance. Abstract: A new strategy was proposed to prepare a composite film using mussel adhesive protein Mefp-1 and graphene to achieve corrosion protection and surface lubrication on carbon steel. The dispersibility of graphene in Mefp-1 solution was firstly investigated and deposition methods of Mefp-1 /graphene film were proposed. In-situ confocal Raman micro-spectroscopy and electrochemical impedance spectroscopy measurements were utilized to study the corrosion inhibition effect in NaCl solution. Friction tests were conducted to study the tribological properties. Results show that the Mefp-1 /graphene film exhibits strong adhesion to carbon steel, provides improved corrosion- and wear-resistance, and a significantly increased lubricity on carbon steel.